Biallelic variants in HTRA2 cause 3-methylglutaconic aciduria mitochondrial disorder: case report and literature review - Gurusamy, Umamaheswaran; Ramadesikan, Swetha; Marhabaie, Mohammad; Colwell, Caitlyn M.; Hunter, Jesse M.; Leung, Marco L.; Mardis, Elaine R.; White, Peter; Manickam, Murugu; Wilson, Richard K.; Koboldt, Daniel C. (Frontiers in Genetics, 2024)
Background: Leigh syndrome is a rare, genetic, and severe mitochondrial disorder characterized by neuromuscular issues (ataxia, seizure, hypotonia, developmental delay, dystonia) and ocular abnormalities (nystagmus, atrophy, strabismus, ptosis). It is caused by pathogenic variants in either mitochondrial or nuclear DNA genes, with an estimated incidence rate of 1 per 40,000 live births. Case presentation: Herein, we present an infant male with nystagmus, hypotonia, and developmental delay who carried a clinical diagnosis of Leigh-like syndrome. Cerebral magnetic resonance imaging changes further supported the clinical evidence of an underlying mitochondrial disorder, but extensive diagnostic testing was negative. Trio exome sequencing under a research protocol uncovered compound-heterozygous missense variants in the HTRA2 gene (MIM: #606441): NM_013247.5:c.1037A>T:p.(Glu346Val) (maternal) and NM_013247.5:c.1172T>A:p.(Val391Glu) (paternal). Both variants are absent from public databases, making them extremely rare in the population. The maternal variant is adjacent to an exon-intron boundary and predicted to disrupt splicing, while the paternal variant alters a highly conserved amino acid and is predicted to be damaging by nearly all in silico tools. Biallelic variants in HTRA2 cause 3-methylglutaconic aciduria, type VIII (MGCA8), an extremely rare autosomal recessive disorder with fewer than ten families reported to date. Variant interpretation is challenging given the paucity of known disease-causing variants, and indeed we assess both paternal and maternal variants as Variants of Uncertain Significance under current American College of Medical Genetics guidelines. However, based on the inheritance pattern, suggestive evidence of pathogenicity, and significant clinical correlation with other reported MGCA8 patients, the clinical care team considers this a diagnostic result. Conclusion: Our findings ended the diagnostic odyssey for this family and provide further insights into the genetic and clinical spectrum of this critically under-studied disorder.